Adipokines, Weight Gain and Metabolic and Inflammatory Markers After Antiretroviral Therapy Initiation: AIDS Clinical Trials Group (ACTG) A5260s. (12th June 2021) - Koethe, John R; Moser, Carlee; Brown, Todd T; Stein, James H; Kelesidis, Theodoros; Dube, Michael; Currier, Judith; McComsey, Grace A
Abstract: Background: The adipokines leptin and adiponectin, produced primarily by adipose tissue, have diverse endocrine and immunologic effects, and circulating levels reflect adipocyte lipid content, local inflammation, and tissue composition. We assessed relationships between changes in regional fat depots, leptin and adiponectin levels, and metabolic and inflammatory markers over 96 weeks in the AIDS Clinical Trials Group (ACTG) A5260s metabolic substudy of the A5257 randomized trial of tenofovir disoproxil fumarate/emtricitabine plus atazanavir/ritonavir, darunavir/ritonavir, or raltegravir among treatment-naive persons with human immunodeficiency virus (PWH). Methods: Fat depots were measured using dual-energy absorptiometry and abdominal computed tomographic imaging at treatment initiation and 96 weeks later. Serum leptin and adiponectin, homeostatic model assessment of insulin resistance (HOMA-IR), and high-sensitivity C-reactive protein (hsCRP) were measured at the same timepoints. Multivariable regression models assessed relationships between fat depots, adipokines, HOMA-IR, and hsCRP at week 96. Results: Two hundred thirty-four participants maintained viral suppression through 96 weeks (90% male, 29% black, median age 36 years). Serum leptin increased over 96 weeks (mean change 22%) while adiponectin did not (mean change 1%), which did not differ by study arm. Greater trunk, limb, and abdominal subcutaneous and visceral fat were associated with higher HOMA-IR and hsCRP at 96 weeks, but serum leptin level was a stronger determinant of these endpoints using a mediation model approach. A similar mediating effect was not observed for adiponectin. Conclusions: Higher circulating leptin is associated with greater HOMA-IR and hsCRP independent of fat depot size, suggesting that greater adipocyte lipid content may contribute to impaired glucose tolerance and systemic inflammation among PWH starting antiretroviral therapy. Abstract : Circulating leptin levels reflect adipocyte lipid content. Among persons with HIV initiating antiretroviral therapy in AIDS Clinical Trials Group A5260s, serum leptin level was a stronger determinant of insulin resistance and systemic inflammation at 96 weeks compared to radiographic measurements of regional adiposity.